2021
DOI: 10.1002/celc.202100402
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Carbonyl Clusters Enable Independent Control of Two Proton Transfer Rates in the Mechanism for Hydrogen Evolution

Abstract: Metal carbonyl clusters (MCC's) are atomically defined nanomaterials which can be characterized using the precise tools of molecular (electro)chemistry. HER mechanisms involve two proton transfer (PT) steps in the catalytic cycle. For HER catalyzed by [Co 11 C 2 (CO) 23 ] 3À (1 3À ), cyclic voltammetry measurements were used to determine the rate for PT1 as k PT1 = 3 × 10 8 M À 1 s À 1 , whereas the rate for PT2 is k PT2 = 3.7 × 10 3 M À 1 s À 1 . The fast, diffusion-limited rate for PT1 is consistent with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Molecular Tafel plots for selected molecular electrocatalysts for production of H 2 . Conditions: [DMF­(H)]­NTf 2 –H 2 O with χ H 2 O = 0.7 (1); [DMF­(H)] + in adiponitrile with 1.1 M H 2 O (2) and 0.5 M H 2 O (3); [4-F 3 CO-C 6 H 4 NH 3 ] + in MeCN (4); [C 6 H 4 NH 3 ] + in MeCN (5); , Tris buffer (pH 7) in water (6); [Et 3 NH] + in MeCN (7); [Et 3 NH] + in DMF (8) . TOFs are the highest value measured, except for 7 and 8, which are theoretical TOFs extrapolated to 1 M acid concentration.…”
Section: Electrocatalytic Production Of H2 With [Ni(p2n2)2]2+ Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular Tafel plots for selected molecular electrocatalysts for production of H 2 . Conditions: [DMF­(H)]­NTf 2 –H 2 O with χ H 2 O = 0.7 (1); [DMF­(H)] + in adiponitrile with 1.1 M H 2 O (2) and 0.5 M H 2 O (3); [4-F 3 CO-C 6 H 4 NH 3 ] + in MeCN (4); [C 6 H 4 NH 3 ] + in MeCN (5); , Tris buffer (pH 7) in water (6); [Et 3 NH] + in MeCN (7); [Et 3 NH] + in DMF (8) . TOFs are the highest value measured, except for 7 and 8, which are theoretical TOFs extrapolated to 1 M acid concentration.…”
Section: Electrocatalytic Production Of H2 With [Ni(p2n2)2]2+ Complexesmentioning
confidence: 99%
“…These three catalysts represent the current state of the art for H 2 production by the [Ni(P 2 N 2 ) 2 ] 2+ catalyst family and are recommended for benchmarking comparisons. Tafel plots for selected examples of other molecular catalysts are shown in Figure 30 for comparison, including the well-known 169 cobaloxime catalyst (4), 164 a highly active [Co 13 C 2 (CO) 24 ] 4− cluster complex (5), 165,166 synthetic model complexes of [FeFe]-hydrogenase (6) 167 and [NiFe]-hydrogenase (7), 167 and an Fe(porphyrin) complex (8). 168 Comparison of the TOF 0 values shows that the [Ni(P 2 N 2 ) 2 ] 2+ catalysts are more active than other molecular catalysts by two orders of magnitude or more.…”
Section: Molecular Tafel Plots For H 2 Productionmentioning
confidence: 99%
“…This electron-sink behavior enables the application of metal carbonyl clusters in electrocatalytic processes . In particular, molecular Fe and Co carbonyl clusters have been employed as electrocatalysts for the two-electron reduction of two protons to molecular hydrogen and for the two-electron reduction of H + and CO 2 to formate. , The molecular nature of these clusters allows us to gain detailed structural insight into the electrocatalytic active species and into the overall mechanism occurring in the catalyst microenvironment . In this sense, the study of larger and larger molecular clusters such as HNMCCs represents an exciting frontier that could create a bridge to contemporary nanomaterials for electronic and electrochemical applications. …”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that the large metal carbonyl clusters promote hydride formation with rate 10 8 M –1 s –1 . We believe that this fast rate has two possible origins. The multiple metal–metal bonds in the clusters serve as multiple sites for protonation, and this should provide a kinetic boost to the rate of cluster-hydride formation. , In addition, the high anionic charges, 3– or 4–, on the clusters promote PT: while the delocalized structures of the clusters enable access to modest reduction potentials relative to single-metal site electrocatalysts, at a given formal oxidation state or overall charge…”
Section: Introductionmentioning
confidence: 99%